Organic Matter and Heavy Metals Leachate Effect on Soils of Selected Dumpsites in Selected North Central States of Nigeria - Musa, J. J.; Bala, J. D.; Mustapha, H. I.; Musa, E. T.; Akos, M. P.; Yerima, Y. I.; Daniel, E. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This research was conducted to assess the presence  of some heavy metals Chromium (Cr), Iron (Fe), Copper (Cu), Manganese (Mn), Lead (Pb), Zinc (Zn) and Aluminum (Al) in municipal solid waste dumps. Heavy metals in the soils were determined at varying depths of 0-5cm, 5-15cm and 15-30cm to assess the extent of pollution and the effects of pH and organic matter in the soil. Heavy metals concentrations were analysed using Atomic Absorption Spectrophotometer. The results revealed a significant difference (p < 0.05) in the concentrations of heavy metals across varying depth at the dumpsites when compared with control points in the same location. Mn had the highest mean 131.22 ± 25.98 mgkg-1 followed by Fe, which is 69 ± 11.02 mgkg-1 at the dumpsites. Mean concentration of all the Heavy metals investigated at the various dumpsites studied were significantly higher than at the control point and below the maximum standard levels set by FAO and WHO for agricultural soils. Result of particle distribution indicated higher sand content (> 80.0%) and lower clay and silt contents in both dumpsite and control site which implies the ease of movement of dissolved metals in the soil environment. Organic Matter (OM) content at dumpsites was observed to be slightly higher than at the control sites. The data also signifies that as pH decreases and %OM decreases the concentration of these heavy metals decreases down the soil profile. It is, therefore, concluded that accumulation of heavy metals in depth was highly correlated with pH and organic matter content.